Situations of internationalization of higher education under the Covid-19 pandemic – a scientometric review - Zhu, Zehao; Abdul Kadir, Suhaida; Abdullah, Arnida (Human Resources Management Academic Research Society (HRMARS), 2023)
The internationalization of higher education (IoHE) is currently facing numerous problems and major changes because of the COVID-19 pandemic. However, a scientometric review of IoHE during and post the pandemic crisis is necessary to guide future research trends. This study employed the CiteSpace visual analysis tool to examine and synthesize IoHE research from 2019 to 2023. Various methodologies, including co-occurrence analysis, co-citation analysis, and cluster analysis, were utilized to accomplish this task. The analysis encompassed 1568 bibliographic entries sourced from the Web of Science and Scopus databases. The results of the study indicated that a significant number of scholars emerged during this particular time frame, with the primary institutions originating primarily from China, the United Kingdom, and the United States. The research themes mostly centered around policy, English medium instruction, e-learning, and the mobility of students and academic staff. As a result, a total of 14 clusters were identified. The future trends of IoHE encompass various aspects, including the establishment of international branch campuses, the implementation of internationalization at home strategies, the development of online education models to enhance educational systems, the promotion of sustainable development through the cultivation of cultural diversity, and the enhancement of teaching quality and intercultural competence.